2008
DOI: 10.1007/s00709-008-0288-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardosins in postembryonic development of cardoon: towards an elucidation of the biological function of plant aspartic proteinases

Abstract: Summary. Following on from previous work, the temporal and spatial accumulation of the aspartic proteinases (EC 3.4.23) cardosin A and cardosin B during postembryonic seed development of cardoon (Cynara cardunculus) was studied. mRNA and protein analyses of both cardosins suggested that the proteins accumulate during seed maturation, and that cardosin A is later synthesised de novo at the time of radicle emergence. Immunocytochemistry revealed that the precursor form of cardosin A accumulates in protein bodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 31 publications
2
46
0
3
Order By: Relevance
“…In addition, rapid extracellular proteolytic events can be expected to take place leading up to the completion of germination, contributing to cell wall loosening and remodeling, relieving the tissue constraints and allowing radicle protrusion. The Cardosin extracellular aspartic proteases have already been implicated in such a process (Pereira et al 2008), and this current study also implicates MMP involvement in the ECM modiWcation required for germination.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, rapid extracellular proteolytic events can be expected to take place leading up to the completion of germination, contributing to cell wall loosening and remodeling, relieving the tissue constraints and allowing radicle protrusion. The Cardosin extracellular aspartic proteases have already been implicated in such a process (Pereira et al 2008), and this current study also implicates MMP involvement in the ECM modiWcation required for germination.…”
Section: Discussionmentioning
confidence: 60%
“…Thus, from this evidence and in the absence of further mRNA analysis, the polypeptides appear to be the products of distinct genes. In addition, it has been shown before that due to the high level of similarity among cardosin A and the cardosin A-like proteins it seems impossible to distinguish between cardosin A and cardosin A-like proteins mRNAs (Pereira et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Endo H digestions were carried out as described by Batoko et al (2000). The Western-blotting procedure was performed as described by Pereira et al (2008). The primary antibody used was raised against a speciWc epitope located in an exposed region of the heavy chain of cardosin B, CVIHPRYDSGD.…”
Section: Sampling and Clsm Analysismentioning
confidence: 99%
“…This result suggested that the mechanisms for protein assembly and transport through the endomembrane system may be tissue dependent. We also suggested cardosin A as a bifunctional enzyme that could participate in the protein processing and/or degradation of seed storage proteins and in membrane lipid conversion during water uptake and solute leakage in actively growing tissues (Pissarra et al 2007;Pereira et al 2008). In addition, it has been suggested that cardosin A, even in its unprocessed form, is an active enzyme since its pro-segment is unable to block access to the catalytic cleft (Simões and Faro 2004).…”
Section: Introductionmentioning
confidence: 96%